Noise exposure assessment of non-coal mining workers in four provinces of China - Wang, Xin; Kang, Ning; Dong, Yiwen; Liu, Kai; Ning, Kang; Bian, Hongying; Han, Feng; Chen, Yongqing; Ye, Meng (Frontiers in Public Health, 2023)
Objective This study aimed to understand the noise exposure of non-coal mines in China to take appropriate controls to protect workers' health. Methods An assessment of non-coal miners' noise exposures was conducted in four provinces in China. Individual noise exposure levels were measured, and the survey on the hearing protector device (HPD) equipment was administered. Results 423 noise dosimeter measurements were obtained, including drilling, blasting, ore drawing, transportation, winching, crushing, screening and ball milling, and auxiliary (air pressure, pump, and maintenance). A total of 31.9% of the individual noise levels (LEX,8h) exceeded 85 dB(A), and the median dosages of non-coal miners with high noise exposure were: excavation workers-89.1 dB(A), mill operators-88.7 dB(A), and crusher operators-87.0 dB(A). The noise dose of underground mine workers is higher than that of surface mine workers (P < 0.001). A total of 53.7% of non-coal mining enterprises are not equipped with HPD for workers, mainly small and micro enterprises. Conclusions High levels of hazardous noise exposure are typical in non-coal mines. Noise exposure data can help to develop more feasible noise controls.